Speed and anaerobic fitness in elite junior basketball players during a pre-competitive mesocycle - Litkowycz, R.; Mikolajec, K.; Zajac, A.; Goralczyk, R. (Studies in Physical Culture and Tourism, 2008)
Starting speed training and anaerobic power are the main components of basketball fitness. While preparing for competition, especially tournaments such as European Championships it is very important to create an optimal balance between training loads directed at the development of speed, anaerobic power and capacity. The main objective of this work was to determine the influence of a six-week pre-competitive mesocycle on speed and anaerobic fitness variables. The research was conducted on 16 elite young players of Polish U-20 Men`s Basketball National Team. The training loads were registered during all practice sessions with the use of heart rate monitors according to specific intensity zones (aerobic, aerobic/anaerobic, lactic anaerobic and alactic anaerobic). The level of speed abilities at distances of 5, 15, 20, 30 and 10×30 m were diagnosed with the use of a laser diode system LDM 300C-Sport. During the six-week pre-competitive mesocycle starting and absolute speed did not improve significantly (5, 15, 20, 30 m), while anaerobic endurance (10×30 m) showed statistically significant changes. A high volume of training loads in the aerobic zone and an inadequate volume of alactic anaerobic metabolism training seems to be the main reason for lack of improvement in the level speed abilities.